Green revolver - Evans, Worthy, 1971- (South Carolina Poetry Book Prize., 2010)
Selected by David Baker, Green Revolver is the fifth annual winner of the South Carolina Poetry Book Prize and the first published collection by Worthy Evans. These verses resulted from a spontaneous outpouring of poems, pent up during a fourteen-year hiatus from the craft during which Evans worked as a professional reporter, writer, and editor. Much informed by the rapid-fire pace and cadence of his journalism background, Evans's narrative poems are grounded in concrete images of our shared reality and explore a range of imaginative versions of the poet as confident or frightened, loving or hateful, bold or timid, lost or profound. These poems seek a distinguishing personal truth-a sense of belonging in a world not altogether welcoming, or even that familiar, where violent impulses are as threatening as workday drudgery. In these daydreams given form, Henry Fonda wields the same authority as Henry V or Ward Cleaver. In this landscape where the familiar arches longingly toward the surreal, a cockeyed visionary might just find the right fantasy with which to escape the stultifying confinement of banal modernity, as represented by corporate office space and khaki dress slacks, army motor pools and basic training maneuvers, sprawling cityscapes and the omnipresent pestering responsibilities of adulthood in postmillennial America.